Increased Paternal Age at Conception Is Associated with Transcriptomic Changes Involved in Mitochondrial Function in Elderly Individuals - Nevalainen, Tapio; Kananen, Laura; Marttila, Saara; Jylhävä, Juulia; Jylhä, Marja; Hervonen, Antti; Hurme, Mikko (PloS one, 2016)
The increased paternal age at conception (PAC) has been associated with autism spectrum disorder (ASD), schizophrenia and other neurodevelopmental disorders, thus raising questions that imply, potential health concerns in the offspring. As opposed to female oogonia, the male germ cells undergo hundreds of cell divisions during the fertile years. Thus, the advanced paternal age is associated with increase of point mutations in the male spermatogonia DNA, implying that this could be the major driving mechanism behind the paternal age effect observed in the offspring. In addition to replication errors, DNA replication fidelity and inefficient DNA repair machinery in the spermatogonia also contribute to the mutagenic load. Our study population consisted of 38 nonagenarians, participants in the Vitality 90+ Study, born in the year 1920 (women n = 25, men n = 13), for whom the parental birth dates were available. The gene expression profile of the study subjects was determined with HumanHT-12 v4 Expression BeadChip from peripheral blood mononuclear cells. We used Spearman's rank correlation to look for the associations of gene expression with paternal age at conception. Associated transcripts were further analyzed with GOrilla and IPA to determine enriched cellular processes and pathways. PAC was associated with the expression levels of 648 transcripts in nonagenarian subjects. These transcripts belonged to the process of mitochondrial translational termination and the canonical pathway of Mitochondrial dysfunction, more specifically of Oxidative phosphorylation. The observed systematic down-regulation of several mitochondrial respiratory chain components implies compromised function in oxidative phosphorylation and thus in the production of chemical energy.